EKOPEMBADIG: DATA-BASED EDUCATION ECOSYSTEM DASHBOARD AS A GOVERNANCE INNOVATION TO INCREASE STUDENT LITERACY IN TULANG BAWANG REGENCY - Ristu Irham; Noverman Duadji; Tina Kartika (Adisam Publisher, 2026)
Tulang Bawang Regency is a condition which this research defines as a broken policy cycle, a condition in which the data is abundant by means of the Rapor Pendidikan and ANBK system, but perpetually fails to access the actors who need it through a form which can be utilized. This study creates and confirms the EKOPEMBADIG Dashboard model, Ekosistem Komunitas Pembelajaran Berbasis Digital, as an management reconstruction intervention that is not only presenting data but converting data into predictive and prescriptive intervention recommendations at the school level. The article implemented a case study methodology using a single instrument with a critical framework and NVivo Project Map analysis, engaging 25 informants from diverse levels of the ecosystem to trace the design logic of EKOPEMBADIG and its discernible impacts on actor capability. The findings indicate that EKOPEMBADIG’s four-layer architecture, from data sources to ETL and validation, analytics, and decision and recommendation, produces measurable changes in the way actors operate in the ecosystem. School principals are transforming from passive administrative executors to evidence-based leaders; teachers are transforming from routine-driven instruction to strategy adjustment based on student profiles; and supervisors are transforming to indicator-based supervision with predictive early warning capacity. The model operationalizes a six-stage data-driven policy cycle and recommends a Regent’s Regulation as the regulatory foundation without which the ecosystem remains dependent on individual leadership continuity rather than institutional architecture. Theoretically, this study adds to the glocal model of human-centered development, theory of change, and distributed leadership in the context of the specific limitations of an Indonesian regency. In practice, EKOPEMBADIG provides a reproducible blueprint for regencies with the same paradox of data abundance without policy consequence.